Penerapan Model Pembelajaran Project Based Learning (PjBL) Berbantuan Poster Dalam Meningkatkan Kemampuan Literasi Lingkungan - purwati, novi (Undiksha, 2023)
This research aims to analyze students' learning activities, examine the differences in environmental literacy improvement, and assess students' responses through the implementation of Project-Based Learning (PjBL) assisted by posters to enhance students' environmental literacy skills in the topic of environmental changes. This study involved two classes, an experimental group, and a control group, with a total of 30 students as the research sample. Data collection techniques included tests, observations, and questionnaires. The research design used was a pretest and posttest control group, with two classes receiving different treatments. The results of this study indicate a significant improvement in students' learning activities when implementing the Project-Based Learning model assisted by posters to enhance students' environmental literacy skills in the topic of environmental changes. The increase in students' learning activities from the second to the third meeting in the experimental class using the PjBL model assisted by posters for environmental change topics was higher compared to the control class. Furthermore, there was a significant difference in the improvement of environmental literacy skills between the experimental and control classes, with a significant result of sig 0.000 < 0.05. It can be concluded that Ho is rejected, and Ha is accepted. The student response questionnaire regarding the implementation of the PjBL model assisted by posters in enhancing environmental literacy skills showed that the average student response score was 72%, with 20% falling into the